Bandung Manufacturing Polytechnic Challenges in Achieving National and International Quality - Supriyadi Sadikin; Kismartini; Retno Sunu Astuti; Hari Susanta (Soshum: Jurnal Sosial dan Humaniora, 2022)
The issue of quality is a critical issue for Polytechnics in Indonesia because of the increasing demands of society on institutional performance, therefore Universities need quality assurance as a measure to assess their success or failure. In this context, the role of leadership in every organization is very dominant in developing and increasing the competitiveness of the organization. This study aims to examine the implementation of the system and formulate a management synchronization strategy between ISO 9001:2015 and SPMI to support SPME BAN-PT. This research uses the desk research method. This research method consists of three main stages, namely the standard interpretation stage, the analysis stage and the standard integration stage. The results of this study indicate that in compiling the synchronization of the ISO 9001:2015 and SPMI systems. From the conformity table of the Integration Structure of QMS ISO 9001:2015 and SPMI, it can be seen that the requirements of the ISO 9001:2015 Quality Management System and SPMI complement each other, following the requirements of the Higher Education accreditation criteria set by BAN-PT. With an integrated quality management system and consistently applied by Polman Bandung management, as a leader in this organization will increase the effectiveness in achieving institutional excellence, increase competitiveness and ensure sustainability in facing challenges and increasingly fierce competition in the world of education, both nationally and internationally.